Study of rainfall - runoff relationship for Langat river watershed by using HEC-HMS - Muhammad Hafizuddin, Md Rasib (2014)
In this era, we always heard about a flood problems occurrence in Malaysia. Malaysia is a country that subjected to flood problems because it was surrounded by South China Sea. In Malaysia, there are some places that have serious flood problems which is a state near with South China Sea such as in Terengganu, Johor and Selangor. Langat River was located near with Selangor and it is connected to the South China Sea. The places near with Langat River always had a flood problem in every year. The thesis is conducted to stimulate the precipitation-runoff processes of dendritic watershed systems. The thesis also prepared validation and verification of HEC- HMS (hydrological model) to recorded data. After these two objectives of study were completed, the appropriate model for flood hydrograph prediction is produce. From the model, hopefully it will help to make a decision to prevent a flood problem. HEC-HMS is a tool to produce a number of hydrologic modeling inputs. It also can be used to recognize the rainfall- runoff relationship of Langat River in a certain period. From the rainfall data, a hydrograph of Langat River can be obtained by using analysis of relationship between rainfall and runoff. This hydrograph are used for studies of urban drainage and flow forecasting. So, it can be guidance to people along Langat River aware about flood problems and also can be flood control management in Langat River. By referring to Root Mean Square Error (RMSE), as the value is near to zero, it is considered as the best fit. The RMSE value obtained for Figure 4.2, Figure 4.13, Figure 4.14 and Figure 4.25 are 0.256 m 3 /s, 0.346 m 3/s, 1.121 M3 /s and 0.319 M3 /s respectively. As for conclusion, SCS Unit Hydrograph method can be used for simulation in Langat River basin.